The State's Injustice: Failing to Protect Fixed-Term Workers' Rights - Arpangi, Arpangi; Sanni, Tajudeen (Journal of Human Rights, Culture and Legal System, 2025)
Labor market flexibility is widely promoted, with fixed-term employment contracts as a key component. However, concerns remain about whether this employment status provides fair protection for workers. This study examines regulatory gaps in Indonesia’s fixed-term employment agreements to assess their fairness and propose ideal legal protections. Using a normative legal research method, this study compares the legal frameworks for fixed-term contract workers in Indonesia, Germany, and Somalia. It applies a normative approach, legislative techniques, and legal system theory to identify weaknesses and recommend fair policies. Findings reveal significant differences in legal protection. Germany enforces strict regulations ensuring worker rights, Indonesia adopts a more flexible system but struggles with weak supervision, while Somalia provides minimal protection due to regulatory gaps. Indonesia’s fixed-term employment regulations remain unfair due to legal loopholes, inadequate labor supervision, and low legal awareness among workers and employers. To address these issues, labor regulations should enhance job security, prevent unilateral termination and discrimination, and strengthen dispute resolution mechanisms. An ideal legal framework must balance worker protections with business flexibility, ensuring fairness while supporting economic growth.